Empowering nurses with technology : a practical guide to nursing informatics - McGrow, Kathleen (Routledge, 2025)
"Nursing informatics is the specialty that integrates nursing science with multiple information management and analytical sciences to identify, define, manage, and communicate data, information, knowledge, and wisdom in nursing practice. It allows nurses to deliver evidence-based and patient-centered care, improve human health and advance medical research. It also enhances clinical workflows so that nurses and other personnel can care for patients more efficiently and effectively. Some of the benefits of nursing informatics include a reduction in medical errors, lower costs, improved nurse productivity, and better care coordination among nurses, physicians, pharmacists, and others throughout various care stages. Empowering Nurses with Technology: A Practical Guide to Nurse Informatics is a comprehensive guidebook for nurses and healthcare professionals looking to understand the role of technology in modern nursing practices. This book covers the basics of healthcare technology, including electronic health records (EHRs), telehealth, and mobile health applications. This book offers practical advice for implementing technology in nursing workflows, as well as strategies for training and engaging nursing staff in the use of new technology. It also explores the impact of technology on patient care and outcomes, discussing topics such as patient safety, privacy, and data security. This book provides a useful resource for nurses seeking to leverage technology to improve the quality and efficiency of their care, while also enhancing their professional development and job satisfaction"-- Provided by publisher.
Keywords: Nursing informatics.; elektronické knihy; electronic books